Long-run commodity prices, economic growth and interest rates: 17th century to the present day - Harvey, David I.; Kellard, Neil M.; Madsen, Jakob B.; Wohar, Mark E. (Elsevier, 2016)
A significant proportion of the trade basket of many developing countries is comprised of primary commodities. This implies relative price movements in commodities may have important consequences for economic growth and poverty reduction. Taking a long-run perspective, we examine the historical relation between a new aggregate index of commodity prices, economic activity and interest rates. Initial empirical tests show that commodity prices present a downward trend with breaks over the entire industrial age, providing clear support for the Prebisch-Singer hypothesis. It would also appear that this trend has declined at a faster rate since the 1870s. Conversely, several GDP series such as World, Chile, China, UK and US, trend upwards with breaks. Such trending behaviour in both commodity prices and economic activity suggests a latent common factor like technological innovation.